RISET DAN PENGEMBANGAN KEILMUAN: SEBUAH PENDEKATAN INTEGRATIF - Machfudz, Masyhuri (Fakultas Ekonomi, UIN Maliki Malang, 2012)
Arranging a research proposal is similar to make a good to sell. A quality research proposal will be continued with a research. If the proposal is clear, the research is easy to conduct. Research is a pious deed (sunnah) from prophet Muhammad SAW, Allah SWT ordered to â€œreadâ€ has a broader meaning, consist of thinking, writing (research), listening, etc. Research result used as evidence for the truth of qouniyah verses in life. Research is conducted either in qualitative or quantitative approach. There are many aspects that need to be considered in recognizing whether the research is qualitative or quantitative. The nature of proposalâ€™s content is not from the title, purposes, variable and analysis method used; at least 32 points need to be considered. Researcher should develop its knowledge as responsibility to be a scientist.